2006
DOI: 10.1007/bf02956768
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation, real-time PCR, metabolites and mycotoxins ofFusarium avenaceum and related species

Abstract: In this paper the latest studies dealing with genetic variation and mycotoxins ofF. avenaceum and related species are reviewed and compared to the data from chromatographic image analyses. Forty-three European strains ofFusarium avenaceum and related species were classified by chromatographic image analysis on full chromatographic matrices. The results were in most cases in agreement with those from morphological and molecular analyses and supported the separation betweenF. avenaceum, F. arthrosporioides andF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…Chromatographic image analysis (Yli-Mattila et al, 2006) has also shown close similarity between the F. acuminatum and F. tricinctum strains. In our study, separation of the F. tricinctum/F.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Chromatographic image analysis (Yli-Mattila et al, 2006) has also shown close similarity between the F. acuminatum and F. tricinctum strains. In our study, separation of the F. tricinctum/F.…”
Section: Discussionmentioning
confidence: 81%
“…They are known as producers of mycotoxins such as enniatins (ENNs) and moniliformin (MON) (Covarelli et al, 2015;Jestoi et al, 2004;Jestoi, 2008). Some authors reported the ability of these species to produce beauvericin Morrison et al, 2002) but more recent studies did not confirm this fact (Kokkonen et al, 2010;Yli-Mattila et al, 2006). Enniatins (ENNs) are cyclic hexadepsipeptides acting as ion channels which are able to cause ionic imbalance in cells, leading to DNA fragmentation and apoptosis (Kamyar et al, 2004;Kouri et al, 2003;Macchia et al, 2002).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The analyzed sorghum and corn samples were EN B free. While mean values in EN B positive ENs and BEA have been detected worldwide, and were generally found in grains contaminated with several Fusarium species (Logrieco et al, 2002;Moretti, Logrieco, Bottalico, Ritieni, & Randazzo, 1994;Plattner & Nelson, 2004;Yli-Mattila et al, 2006).…”
Section: Occurrence Of Ens Bea and Fus In Analyzed Samplesmentioning
confidence: 98%
“…Noteworthy, the species are clustered in strict accordance with their mycotoxin patterns, i.e. A trichothecenes producers (F. sporotrichioides, F. langsethiae) Data on interspecies polymorphism of specific DNA loci facilitates the development highly specific detection system for Fusarium pathogens based on classical PCR or its modification [52][53][54][55][56][57][58][59][60][61]. Routine application of these systems provides rapid and accurate identification of a pathogen at different levels (species, subspecies or species groups depending on the task), and hence allows to predict the potentially accumulated mycotoxins.…”
mentioning
confidence: 99%